Multiple Fluorescence-Based PCR-SSCP Analysis Using Internal Fluorescent Labeling of PCR Products. (September 1996) - Iwahana, H.; Fujimura, M.; Takahashi, Y.; Iwabuchi, T.; Yoshimoto, K.; Itakura, M.
The method to internally label PCR products with multiple colored fluorescent dyes was developed and applied to multiple fluorescence-based PCR single-stranded conformational polymorphism (MF-PCRSSCP) analysis. PCR-amplified fluorescent DNA fragments, which were internally labeled by adding fluorescent dUTPs ([F]dUTPs) to the PCR mixture, were heatdenatured and applied to a nondenaturing polyacrylamide gel (SSCP gel) set on an automated DNA sequencer with a gel temperature-controlling system. The image data were analyzed by GENESCAN TM 672 software . In spite of differences in species and amount of integrated [F]dUTPs, the SSCP profiles were not significantly affected, even by the different labeling methods used—internal labeling or post-labeling at the 3′ ends—in regard to the three different [F]dUTPs examined. However, the salt concentration of the solution containing the DNA samples affected the SSCP profiles. The internally labeled [F]dUTP-containing DNA fragments beyond 1000 bp in length were successfully digested with restriction endonucleases and subjected to SSCP analysis. MF-PCR-SSCP analysis with internal fluorescence labeling affords a simple and sensitive method to detect alterations in DNA sequences.